Prohibited religious assosiations in Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
In the bill of the RK religious associations it is ﬁ xed that the state is separated from religion. In this article the accent is made on those organizations whose activity Vessels RK are forbidden in Kazakhstan by the decision of Supreme Court. Psychological inﬂ uence of group on the individual, and also about the occult and pagan groups operating in the territory of our country, including dangerous to the personality and society are analyzed the reasons of a ban of activity of data of the organizations and the reason manifestation of acts of terrorism, so on. Currently, the number of forbidden religious orgagnization in RK are 16. In article the author comes to a conclusion that it is ﬁ xed in the Constitution of Kazakhstan that it is the independent and secular state therefore any religious association calling for violence, to overthrow of the constitutional system, vliyayushche on mentality of the person doesn't take place in society. Keywords: terrorism, extremism, radicalism, tolerance, religious association.